(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In this article, we will consider solving examples of the topic “the concept of proof”, one of the topics of discrete mathematics and mathematical logic that challenge most students. Knowing the subject of “axioms of reasoning calculus” is of great importance in inducing provable formulas. Through this article, we will show students how to easily prove induction formulas using a feedback account.